Entrepreneurial intention among women: A case study in the Portuguese academy - Gomes, Sofia (2022)
A growing interest in academic entrepreneurship has characterized the past few years. Young university students are increasingly encouraged to create their compa- nies to boost their region's social and economic development. In this regard, women entrepreneurs have been playing a decisive role. They have been increasing in num- ber, becoming of key importance due to their status and significance for the gender impact on entrepreneurship. This research evaluates women's entrepreneurial inten- tion in the Portuguese academy, denoting which entrepreneurial intent is influenced by environmental factors such as closer valuation and social valuation and motiva- tional factors such as attitude toward the behavior, subjective norms, and perceived behavioral control. For this purpose, a quantitative methodology was used. A ques- tionnaire was applied to 731 female students of higher education in Portugal. The analysis of the results allowed us to perceive which variables under study influenced the entrepreneurial intention. The findings will reinforce the literature, thus, contrib- uting to strengthening the theoretical framework on entrepreneurial intentions in women and launching clues for action within public decision-makers, universities, and civil society, allowing to adopt practices that will increase entrepreneurship in women. To our knowledge, this research is one of the few studies on female entre- preneurial intention in academia in a peripheral region of Europe such as Portugal.